Analysis of Interarch Tooth Size Relationship in Nepalese Subjects with Normal Occlusion and Malocclusions. (18th November 2019) - Mishra, Rajeev Kumar; Kafle, Dashrath; Gupta, Rahul
Abstract : Introduction . A proportional relationship between the maxillary and mandibular teeth size is required for achieving good finish with proper overjet and overbite postorthodontic treatment. The aims and objectives of this study were to determine the anterior and overall Bolton's ratio in Nepalese population, to compare Bolton's ratio between subjects with normal occlusion, Class I malocclusion, and Class II malocclusion, to compare these results with Bolton's norm, and to determine the frequency of clinically significant (beyond 2 SD) tooth size discrepancy compared to Bolton's norm. Materials and Methods . The study models of the subjects with normal occlusion and Angle's Class I malocclusion and Class II malocclusion and fulfilling the inclusion criteria were retrieved from department archives. An electronic digital caliper was used to measure mesiodistal tooth size of the maxillary and mandibular teeth anterior to the second molars. The study sample of 120 study models consisted of the normal occlusion group ( n  = 31), Class I malocclusion group ( n  = 47), and Class II malocclusion group ( n  = 42). These measurements were then used to obtain Bolton's ratio in three groups of subjects. Bolton's ratio of study groups was compared with each other and with Bolton's original ratio. Results . The differences in tooth size ratio of the study groups were not significant statistically, when the groups were compared on the basis of malocclusion or gender. Statistically significant differences were exclusively observed between the study groups and Bolton's original sample for the anterior ratio. The frequency of the clinically significant tooth size ratio discrepancy was lower for the overall ratio (9.1%) compared to the anterior ratio (22.5%). Conclusions . Bolton's analysis on the Nepalese population sample shows that there was no significant difference observed on the anterior and overall tooth size ratios when these were compared based on Angle's malocclusion classes or gender. The clinically significant anterior tooth size discrepancy was more prevalent than that of the overall ratio.